Thin Capitalization, Komisaris Independen, dan Capital Intensity Terhadap Tax Avoidance: Peran Moderasi Kepemilikan Institusional - Panesa, Inggrid; Averio, Thomas (ARBITRASE: Journal of Economics and Accounting, 2025)
This study aims to comprehensively examine the impact of thin capitalization, independent commissioners, and capital intensity on tax avoidance practices, with institutional ownership as a moderating factor. The data were obtained from the annual financial statements of companies listed in the LQ45 index during the 2020–2024 period. The analysis was conducted using multiple linear regression and moderation regression analysis (MRA) with IBM SPSS version 26, to thoroughly test the relationships between variables. The research population consisted of 45 companies, with samples selected using purposive sampling according to predetermined inclusion criteria. The results indicate that thin capitalization, independent commissioners, and capital intensity does have an effect on tax avoidance but not significant. Meanwhile, institutional ownership has the potential to moderate the relationship between these three variables and tax avoidance. These findings provide both conceptual and practical implications for the development of literature on tax avoidance and can serve as a reference for company management and policymakers in formulating more effective tax management strategies.